Pengaruh Fragmentasi Hasil Peledakan Batugranit Terhadap Produktivitas Hopper Crusher Di PT Bumi Warna Agung Perkasa Desa Air Mesu Kabupaten Bangka Tengah - Bobby Bagaskara; Janiar Pitulima; Delita Ega Andini (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2018)
The destroyed process or to split the rock with blasted system have effective value and good economic compared with mechanical tools method. Blasted activity effective become is anothere standard the success of activity loading processing to influence achievement targets of mining productivity. This research aim to increasing the productivity hopper crusher baited rate and minimize total percentage of boulder, so that material reduction activity in hopper crusher become was more effective. The study was on 14 blasted is project from PT Bumiwarna Agung Perkasa. Data this research consist of geometry, blasted fragmentation, cycle time loading hopper. This research used method with geometry an estimates used R.L.Ash method with fragmentation analysis used Kuz-Ram and image analysis. From analysis data there is actual fragmentation 74.680% base on Kuz-Ram and 64.942% base on image analysis with an actual boulder total Kuz-Ram 25.320 % and 35.057% base on image analysis, with result the average time reduction 8.21 minute and an average productivity 131.80 m3/hour. It is minimize total percentage of boulder, needed to revise blasted geometry based on R.L. Ash theory with reduction boulder size >80 cm by 12.042% with keep the target volume production 40026.8 BCM. It is productivity hopper crusher may work better.